Preconditions for improving the management system of innovative marketing of service sector organizations - Ron, Ya. O. (National Technical University "Kharkiv Polytechnic Institute", 2025)
The purpose of the research is to develop and improve methods and tools of innovative marketing for the services sector, which will allow to meet challenges and consumer needs, as well as to improve the competitiveness of business entities. The proposed methods should contribute to strengthening the adaptability of marketing activities as a response to technological and economic changes at the global level.
Keywords: innovative marketing; service sector; management system